2018
DOI: 10.1001/jamaneurol.2018.0278
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-A*31:01 Screening With the Incidence of Carbamazepine-Induced Cutaneous Adverse Reactions in a Japanese Population

Abstract: for the GENCAT Study Group IMPORTANCE Carbamazepine, a commonly used antiepileptic drug, is one of the most common causes of cutaneous adverse drug reactions (cADRs) worldwide. The allele HLA-A*31:01 is reportedly associated with carbamazepine-induced cADRs in Japanese and European populations; however, the clinical utility of HLA-A*31:01 has not been evaluated.OBJECTIVE To assess the use of HLA-A*31:01 genetic screening to identify Japanese individuals at risk of carbamazepine-induced cADRs.DESIGN, SETTING, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 31 publications
1
36
3
1
Order By: Relevance
“…Indeed, our meta‐analysis shows that HLA‐A*31:01 carriers have eightfold higher risk of developing CBZ‐SCAR than noncarriers. Interestingly, a recent prospective study in Japan was able to show that pre‐prescription genotyping for HLA‐A*31:01 reduces the incidence of CBZ hypersensitivity reactions . Taken together, the overwhelming evidence of the role of HLA‐A*31:01 in predisposing to CBZ‐SCAR shows that there is a need to implement its use in clinical settings, as outlined in the recent Clinical Pharmacogenetics Implementation Consortium guideline .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our meta‐analysis shows that HLA‐A*31:01 carriers have eightfold higher risk of developing CBZ‐SCAR than noncarriers. Interestingly, a recent prospective study in Japan was able to show that pre‐prescription genotyping for HLA‐A*31:01 reduces the incidence of CBZ hypersensitivity reactions . Taken together, the overwhelming evidence of the role of HLA‐A*31:01 in predisposing to CBZ‐SCAR shows that there is a need to implement its use in clinical settings, as outlined in the recent Clinical Pharmacogenetics Implementation Consortium guideline .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent prospective study in Japan was able to show that pre-prescription genotyping for HLA-A*31:01 reduces the incidence of CBZ hypersensitivity reactions. 19 Taken together, the overwhelming evidence of the role of HLA-A*31:01 in predisposing to CBZ-SCAR shows that there is a need to implement its use in clinical settings, as outlined in the recent Clinical Pharmacogenetics Implementation Consortium guideline. 20 Independent of the HLA-A*31:01 association, we identified a residual effect in the MHC region mapping to MUC22 gene (lead SNP rs116071718).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice records demonstrated that identification of population at high risk and the subsequent elimination of offending drugs were effective to prevent drug-induced hypersensitivity syndrome. To date, prospective screening of genetic risk factors (especially HLA alleles) for incidence reduction of drug-induced hypersensitivity syndrome has been adopted into routine clinical practice, such as HLA-B*15:02 and HLA-B*31:01 for carbamazepine induced Stevens-Johnson syndrome, toxic epidermal necrolysis or cutaneous adverse reactions,19 20 HLA-B*57:01 testing to prevent abacavir induced adverse drug reaction with eosinophilia and systemic symptoms21 and HLA-B*58:01 for allopurinol induced severe cutaneous adverse reactions 22. In the present study, HLA-B*13:01 was used as a predictor exhibiting excellent performance to discriminate the TCE-exposed workers at high risk for TIHS with the sensitivity of 75% and specificity of 91.1%.…”
Section: Discussionmentioning
confidence: 99%
“…85 The predicted cost effective benefits of HLA-A*31:01 screening suggest a need to test between 47-67 individuals of either Caucasian or Japanese descent to avoid a single cADR case, 88 and testing has resulted in a 40% decreased incidence of carbamazepine-induced cADRs in the latter population. 89 Given the rising incidence of reported HLA-A*31:01-related AED-induced cADRs there is accumulating evidence to support pre-treatment genetic screening in at risk populations.…”
Section: Hla Linkage and Aed-t-cell Crossreactivitymentioning
confidence: 99%